1999
DOI: 10.1046/j.1365-2672.1999.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofBacillus thuringiensisserovarbolivia(serotype H63), a novel serovar isolated from the Bolivian high valleys

Abstract: The type strain Bacillus thuringiensis var. bolivia (serotype H63), isolated from the Bolivian high valleys, has been characterized at different levels. Its parasporal crystal has an unusual shape and it is composed of a protein of 155 kDa which shows two bands of 75 and 80 kDa after activation. Analysis by PCR shows the presence of cry1 genes, and amplification with specific primers gave products for cry1E, cry1D, cry4 A and cry4B with sizes different to those expected. Immunoblotting tests showed positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The introduction of serotypes based on fl agellar antigens (H-antigen) serotyping along with biochemistry characters helped the description of new Bt serotypes (Bonnefoi and De Barjac, 1963;De Barjac and Franchon, 1990). The commercial interest in biological control of insects stimulated intensive screening programs to search for new strains in different countries, allowing the discovery of new serovars presenting different spectrums of entomopathogenic activity (Kawalek et al, 1995;Rabinovitch et al, 1995;Seleena et al, 1995;Orduz et al, 1996;Ferrandis et al, 1999). In the 1990's, 82 different fl agellar serovars, 69 serotypes and 13 sub-antigens groups of Bt were identifi ed.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of serotypes based on fl agellar antigens (H-antigen) serotyping along with biochemistry characters helped the description of new Bt serotypes (Bonnefoi and De Barjac, 1963;De Barjac and Franchon, 1990). The commercial interest in biological control of insects stimulated intensive screening programs to search for new strains in different countries, allowing the discovery of new serovars presenting different spectrums of entomopathogenic activity (Kawalek et al, 1995;Rabinovitch et al, 1995;Seleena et al, 1995;Orduz et al, 1996;Ferrandis et al, 1999). In the 1990's, 82 different fl agellar serovars, 69 serotypes and 13 sub-antigens groups of Bt were identifi ed.…”
Section: Introductionmentioning
confidence: 99%
“…piercei (Ferrandis et al 1999, Uribe et al 2003, Martínez O. and Cerón S. 2004, Hernández et al 2005. Though, using the same toxin, Gomez et al (2000) observed after 5 days a mortality of 43 to 49% on neonate larvae of P. vorax when 70µg/ml of the purified toxin was applied on the surface of an artificial medium.…”
Section: Biological Controlmentioning
confidence: 93%